Antiseptic mouthwash for gonorrhoea prevention (OMEGA): a randomised, double-blind, parallel-group, multicentre trial. Issue 5 (May 2021) - Chow, Eric P F; Williamson, Deborah A; Hocking, Jane S; Law, Matthew G; Maddaford, Kate; Bradshaw, Catriona S; McNulty, Anna; Templeton, David J; Moore, Richard; Murray, Gerald L; Danielewski, Jennifer A; Wigan, Rebecca; et al.
Summary: Background: To address the increasing incidence of gonorrhoea and antimicrobial resistance, we compared the efficacy of Listerine and Biotène mouthwashes for preventing gonorrhoea among men who have sex with men (MSM). Methods: The OMEGA trial was a multicentre, parallel-group, double-blind randomised controlled trial among MSM, done at three urban sexual health clinics and one general practice clinic in Australia. Men were eligible if they were diagnosed with oropharyngeal gonorrhoea by nucleic acid amplification test (NAAT) in the previous 30 days or were aged 16–24 years. They were randomly assigned to receive Listerine (intervention) or Biotène (control) via a computer-generated sequence (1:1 ratio, block size of four). Participants, clinicians, data collectors, data analysts, and outcome adjudicators were masked to the interventions after assignment. Participants were instructed to rinse and gargle with 20 mL of mouthwash for 60 s at least once daily for 12 weeks. Oropharyngeal swabs were collected by research nurses every 6 weeks, and participants provided saliva samples every 3 weeks, to be tested for Neisseria gonorrhoeae with NAAT and quantitative PCR. The primary outcome was proportion of MSM diagnosed with oropharyngeal N gonorrhoeae infection at any point over the 12-week period, defined as a positive result for either oropharyngeal swabs or saliva samples by NAAT, and the cumulative incidence of oropharyngeal gonorrhoea at the week 12 visit. A modified intention-to-treat analysis for the primary outcome was done that included men who provided at least one follow-up specimen over the 12-week study period. The trial was registered on the Australian and New Zealand Clinical Trials Registry (ACTRN12616000247471). Findings: Between March 30, 2016, and Oct 26, 2018, 786 MSM were screened and 256 were excluded. 264 MSM were randomly assigned to the Biotène group and 266 to the Listerine group. The analysis population included 227 (86%) men in the Biotène group and 219 (82%) in the Listerine group. Oropharyngeal gonorrhoea was detected in ten (4%) of 227 of MSM in the Biotène group and in 15 (7%) of 219 in the Listerine group (adjusted risk difference 2·5%, 95% CI −1·8 to 6·8). The cumulative incidence of oropharyngeal gonorrhoea at the week 12 visit did not differ between the two mouthwash groups (adjusted risk difference 3·1%, 95% CI −1·4 to 7·7). Interpretation: Listerine did not reduce the incidence of oropharyngeal gonorrhoea compared with Biotène. However, previous research suggests that mouthwash might reduce the infectivity of oropharyngeal gonorrhoea; therefore, further studies of mouthwash examining its inhibitory effect on N gonorrhoeae are warranted to determine if it has a potential role for the prevention of transmission. Funding: Australian National Health and Medical Research Council.